2012
DOI: 10.1007/s12559-012-9168-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Automatic Detection of Obstructive Sleep Apnea Through Nonlinear Analysis of Sustained Speech

Abstract: We present a novel approach for the detection of severe obstructive sleep apnea (OSA) based on patients' voices introducing nonlinear measures to describe sustained speech dynamics. Nonlinear features were combined with state-of-the-art speech recognition systems using statistical modeling techniques (Gaussian mixture models, GMMs) over cepstral parameterization (MFCC) for both continuous and sustained speech. Tests were performed on a database including speech records from both severe OSA and control speakers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Although poor sleep quality has been associated with cognitive decline ( Lim et al, 2013 ), no such associations have been reported with connected language. However, sustained speech analysis was able to detect participants with obstructive sleep apnea (OSA) with 89% accuracy ( Blanco et al, 2013 ), so it is possible that a more detailed speech and voice analysis may yield more information about the relationship between sleep quality and discourse features. Anxiety has been associated with increases in dysfluency in persons who stutter ( Yang et al, 2017 ), and with pragmatic language difficulties ( Cummings, 2007 ), but research is lacking regarding the relationship between anxiety and connected language in the general population or in persons with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Although poor sleep quality has been associated with cognitive decline ( Lim et al, 2013 ), no such associations have been reported with connected language. However, sustained speech analysis was able to detect participants with obstructive sleep apnea (OSA) with 89% accuracy ( Blanco et al, 2013 ), so it is possible that a more detailed speech and voice analysis may yield more information about the relationship between sleep quality and discourse features. Anxiety has been associated with increases in dysfluency in persons who stutter ( Yang et al, 2017 ), and with pragmatic language difficulties ( Cummings, 2007 ), but research is lacking regarding the relationship between anxiety and connected language in the general population or in persons with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…So far, either due to small samples or subjective judgements, it is hard to quantify up to what extent or under what circumstances we might consider voice as a good discrimination measure between OSA and healthy subjects. Recent efforts such as [6] try to model the upper-airway in OSA subjects as compared to controls by employing computational fluid dynamics models, and they conclude that there is a clear tendency to closure of the upper-airway in OSA. As the upper-way coincides in part with the vocal tract, the thinning of the lumen and tendency to closure experienced in OSA do suggest that there may be an identifiable dysfunction in voice also.…”
Section: Introductionmentioning
confidence: 99%
“…They obtain best results with i-vectors and SVR with linear kernel. Blanco et al introduce a novel method to detect OSA based on patient's voices [29] on the manually collected dataset. In [30], Aydogan et al performs visual scoring of 74 patients using two methods, namely morphological filter and ANN-based to diagnose OSA.…”
Section: Related Workmentioning
confidence: 99%